Determinants of environmental sustainability: Evidence from Saudi Arabia - Omri, Anis; Euchi, Jalel; Hasaballah, Abdel Hafiez; Al-Tit, Ahmad (The Science of the total environment, 2019)
Policymakers in many developing countries are facing pressures between the needs of environmental sustainability. In this context, the present article aims to examine the determinants of environmental sustainability in Saudi Arabia by addressing the following two questions: Is there an EKC in Saudi Arabia? Does financial development, human development, FDI, and trade openness lead to environmental improvement in Saudi Arabia? The empirical findings show that (i) per capita income, financial development, FDI and foreign trade positively contributes to environmental degradation; (ii) EKC hypothesis is validated in the case of Saudi Arabia; (iii) environmental degradation is very sensitive to the levels of financial development, FDI, and foreign trade; and corresponding thresholds were calculated. Policy makers in Saudi Arabia are invited to augment these variables at the level of the calculated thresholds (turning point) to attain the desired impact on environmental improvement. [Display omitted] •Our finding shows that financial development, GDP, FDI and trade contribute negatively to environmental quality.•We also confirm the validity of EKC hypothesis in Saudi Arabia.•Inverted U-shape relationships are found between emissions and the variables FDI, financial development, and trade.•Corresponding thresholds are calculated and discussed.